Mannose as a biomarker of coronary artery disease: Angiographic evidence and clinical significance. (1st January 2022) - Ferrannini, Ele; Marx, Nikolaus; Andreini, Daniele; Campi, Beatrice; Saba, Alessandro; Gorini, Marco; Ferrannini, Giulia; Milzi, Andrea; Magnoni, Marco; Maseri, Attilio; Maggioni, Aldo P.; Burgmaier, Mathias; et al.
Abstract: Background: High mannose has previously associated with insulin resistance and cardiovascular disease (CVD). Our objective is to establish whether mannose is associated with anatomical evidence of coronary artery disease (CAD). Methods: Plasma mannose concentrations were measured by liquid chromatography/tandem mass spectrometry in a discovery cohort ( n = 513) and a validation cohort ( n = 221) of carefully phenotyped individuals. In both cohorts CAD was quantitated using state-of-the-art imaging techniques (coronary computed coronary tomography angiography (CCTA), invasive coronary angiography and optical coherence tomography). Information on subsequent CVD events/death was collected. Associations of mannose with angiographic variables and biomarkers were tested using univariate and multivariate regression models. Survival analysis was performed using the Kaplan-Meier estimator. Results: Mannose was related to indices of CAD and features of plaque vulnerability. In the discovery cohort, mannose was a marker of quantity and quality of CCTA-proven CAD and subjects with a mannose level in the top quartile had a significantly higher risk of CVD events/death ( p = 3.6e-5). In the validation cohort, mannose was significantly associated with fibrous cap thickness < 65 μm (odds ratio = 1.32 per each 10 μmol/L mannose change [95% confidence interval, 1.05–1.65]) and was an independent predictor of death (hazard ratio for mannose≥ vs < 84.6 μmol/L: 4.0(95%CI, 1.4–11.3), p = 0.006). Conclusion: The current data add novel evidence that high mannose is a signature of CAD with a vulnerable plaque phenotype, consistently across measures of severity of vessel involvement and independent of the traditional correlates of CVD, and that it is an independent predictor of incident adverse outcomes. Highlights: High mannose concentration is emerging as a novel marker of cardiovascular disease In the discovery cohort, mannose was a marker of coronary artery disease (CAD). In the validation cohort, mannose was associated with fibrous cap thickness. In both cohorts high mannose was an independent predictor of adverse outcomes. High mannose might be a signature of CAD with a vulnerable plaque phenotype.